Exploring the electronic modulation in controlling the activity and selectivity of Ni-Au-In based catalyst in atmospheric pressure CO2 hydrogenation - Bajpai, Jyotsna P.; Gupta, Sharad; Goud, Devender; Deka, Diku Raj; V. Jagtap, Anuradha; Kumar, Pawan; Ahamed, Momin; Peter, Sebastian C.; Vinod, C. P. (Chemical Engineering Journal, 2025)
Nickel-based catalysts are widely used for the hydrogenation of CO2 but encounter stability challenges during prolonged reactions and at elevated temperatures. At atmospheric pressure, nickel primarily promotes methane formation in CO2 hydrogenation reactions. In this work, we demonstrate that the stability and activity of nickel can be significantly enhanced through gold (Au) modification. Furthermore, we achieve a near-complete selectivity switch from methane to CO by incorporating indium (In), mediated through the formation of Au-In alloy. This catalyst exhibits excellent CO2 conversion and CO selectivity at relatively lower temperatures (400 degrees C), addressing a major bottleneck in the Reverse Water-Gas Shifts (RWGS) reaction. XPS studies demonstrate an interesting electron transfer mechanism facilitated by gold, which involves the formation of electronrich Au species (Au delta-) and the development of Au-In alloys. This process improves the reducibility of nickel oxide while allowing a fraction of nickel to remain in its metallic form, managing a facile hydrogenation process and regulating the shift in selectivity from CH4 to CO.
Keywords: Alloy formation; Bimetallic catalyst; CO2 hydrogenation; RWGS; Selectivity switch; synergy; Trimetallic catalyst; XPS (X-ray photoelectron spectroscopy)